2013
DOI: 10.5194/acpd-13-17519-2013
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Regional nitrogen oxides emission trends in East Asia observed from space

Abstract: Due to changing economic activity, emissions of air pollutants in East Asia change rapidly in space and time. Monthly emission estimates of nitrogen oxides derived from satellite observations provide valuable insight in the evolution of anthropogenic activity on a regional scale. We present the first results of a new emission estimation algorithm, specifically designed to use daily satellite observations of column concentrations for fast updates of emissions of short-lived atmospheric constituents on a~… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…In the first panel, the red dotted line is the hybrid posterior emissions over East China (18–50°N, 102–132°E); the magenta line in the first panel is the bottom‐up anthropogenic emissions from the MEIC inventory plus GEOS‐Chem prior natural emissions; the yellow line is the bottom‐up anthropogenic emissions from Xia et al [] plus GEOS‐Chem prior natural emissions. The cyan dotted line in the first panel is the top‐down estimate for total emissions in East China (18–50°N, 102–132°E) from Mijling et al [].…”
Section: Long‐term Hybrid Inversion With Real Observationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the first panel, the red dotted line is the hybrid posterior emissions over East China (18–50°N, 102–132°E); the magenta line in the first panel is the bottom‐up anthropogenic emissions from the MEIC inventory plus GEOS‐Chem prior natural emissions; the yellow line is the bottom‐up anthropogenic emissions from Xia et al [] plus GEOS‐Chem prior natural emissions. The cyan dotted line in the first panel is the top‐down estimate for total emissions in East China (18–50°N, 102–132°E) from Mijling et al [].…”
Section: Long‐term Hybrid Inversion With Real Observationsmentioning
confidence: 99%
“…These forms of air pollution lead to decreased visibility [ Haagen‐Smit , ], cardiac and respiratory morbidity [ Bhatnagar , ; Ghio et al , ; Nel , ], and acidification and eutrophication of waters when deposited in excess [ Driscoll et al , ; Likens et al , ]. Though NO x emissions in North America [ Kim et al , ; Lamsal et al , ; Russell et al , ; Lu et al , ] and Western Europe [ Castellanos and Boersma , ] have decreased in the past two decades, their emissions in China have increased rapidly due to economic development and urbanization since the turn of the century [ Stavrakou et al , ; Lamsal et al , ; Lin and McElroy , ; Zhao et al , ; Mijling et al , ; Jin and Holloway , ; Krotkov et al , ; Cui et al , ; Duncan et al , ; Xia et al , ].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the four‐dimensional variational (4D‐Var) method (e.g., Elbern et al, , ; Henze et al, , ) has been compared with the mass balance approach (e.g., Boersma et al, ; Martin, Jacob, Chance, et al, ; Toenges‐Schuller et al, ) in Qu et al (), and a hybrid 4D‐Var/mass balance method has been developed to derive top‐down NO x emissions for China from 2005 to 2012. Extended Kalman filter (e.g., Ding, van der A, et al, ; Mijling et al, ) and ensemble Kalman filter (e.g., Miyazaki et al, ) are employed to estimate multiyear NO x emissions in China. 4D‐Var (e.g., Qu et al, ; Wang et al, ; Xu et al, ), mass balance (e.g., Koukouli et al, ; Lee et al, ), and plume methods (e.g., Fioletov et al, ; McLinden et al, ) have also been applied to derive SO 2 emissions from OMI SO 2 and Moderate Resolution Imaging Spectroradiometer aerosol optical depth (AOD) observations.…”
Section: Introductionmentioning
confidence: 99%
“…Mijling et al . [] showed that NO x emissions continued to rise in East China through 2011, though there were reductions in Japan and South Korea. Fischer et al .…”
Section: Resultsmentioning
confidence: 99%